Influence of Self Control on Financial Behaviour and Financial Well-Being Mediated by Optimism - Fowzia Noor Mengal,; Hadi Hassan Khan,; Manzoor Ali,; Wahab Ahmed, (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: This study aims to explore the influence of self-control on financial behaviour and financial well-being. Additionally, it examines the mediating role of optimism in these relationships. Design/Methodology/Approach: The research adopts a quantitative, cross-sectional design. The target population comprises the general public residing in Balochistan. Convenience sampling was employed due to the absence of a sampling frame. The structured questionnaire using a variance-based structural equation modeling (SEM) through the Smart PLS software. Research findings: The results indicate a positive relationship between self-control and financial behaviour and financial security, while selfcontrol negatively correlates with financial anxiety. Furthermore, optimism is an effective mediator between self-control and financial behaviour as well as between self-control and financial anxiety. However, optimism does not significantly impact financial security. Theoretical contribution/Originality: This study contributes to behavioural finance literature by providing a nuanced understanding of how self-control and optimism interact to influence financial behaviour and financial well-being. It adds to the theoretical framework by highlighting the mediating role of optimism in these relationships. Practitioner/Policy implications: The financial educators, policymakers, and practitioners may leverage the understanding of self-control and optimism to design educational programmes and interventions that enhance individuals’ financial behaviours and mitigate financial anxiety. Research limitation: The cross-sectional design limits the ability to assess causality and long-term effects. Future research should consider longitudinal studies to better understand the enduring impacts of selfcontrol and optimism on financial behaviour and well-being.